2015
DOI: 10.4155/fso.15.49
|View full text |Cite
|
Sign up to set email alerts
|

Barberry's ( Berberis integerrima ) ingredients suppress T-cell response and shift immune responses toward Th2: an in vitro study

Abstract: Aim:Food and medicinal applications of barberry date back to 2500 years ago. This study investigates Berberis integerrima impact on lymphocytic immune responses.Materials & methods:Balb/c splenocytes were treated by 0.001–1000 μg/ml of B. integerrimaaqueous and alcoholic extracts in presence of phytohemagglutinin and lipopolysaccharide mitogens. Cell proliferation was assayed and cytokines were measured using ELISA.Results:Both extracts suppressed proliferation of phytohemagglutinin stimulated splenocytes (as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Although biological and therapeutic effects of barberry have been reported by other researchers in the past, its effect on the immune system is not properly investigated (Bhardwaj & Kaushik, 2012; Hosseinzadeh, Ramezani, Shafaei, & Taghiabadi, 2013). Previous studies in traditional and current medicine suggest that barberry has diverse effects on the immune system (Fateh, Dibazar, & Daneshmandi, 2015). Apparently, black barberry can change the cytokine production pattern in lymphocytes, suppress T‐cell proliferation, and enhance β‐cell expansion (Ho et al, 2009; L. Wang et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although biological and therapeutic effects of barberry have been reported by other researchers in the past, its effect on the immune system is not properly investigated (Bhardwaj & Kaushik, 2012; Hosseinzadeh, Ramezani, Shafaei, & Taghiabadi, 2013). Previous studies in traditional and current medicine suggest that barberry has diverse effects on the immune system (Fateh, Dibazar, & Daneshmandi, 2015). Apparently, black barberry can change the cytokine production pattern in lymphocytes, suppress T‐cell proliferation, and enhance β‐cell expansion (Ho et al, 2009; L. Wang et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In this clinical trial, barberry extract was found to be effective in increasing IL‐10 levels in RA patients. Fateh et al reported that aqueous and alcoholic barberry extract enhanced IL‐10 and TGF‐β release from splenocytes (Fateh et al, 2015). It is suggested that barberry may shift the Th1/Th2 balance towards Th2 polarization, which means that it changes the cytokine release pattern and increases cytokines produced by Th2 or Tregs, such as IL‐10 (Chueh & Lin, 2012; Fateh et al, 2015; Lin & Lin, 2011).…”
Section: Discussionmentioning
confidence: 99%